If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18c = c + -13 Reorder the terms: -18c = -13 + c Solving -18c = -13 + c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. -18c + -1c = -13 + c + -1c Combine like terms: -18c + -1c = -19c -19c = -13 + c + -1c Combine like terms: c + -1c = 0 -19c = -13 + 0 -19c = -13 Divide each side by '-19'. c = 0.6842105263 Simplifying c = 0.6842105263
| -2(4x-5)+6(2x+1)=8 | | a/5=-13 | | 7y-9=6 | | 200-2x=130 | | .6x^2-.6x+4.2=0 | | 8.50x-2.6=5.9 | | 4(2-7)=3x | | 3x^2=28x-64 | | 6(n-10)=5n-42-2n | | y^2-10y-12x+37=0 | | 4m^2+3m-22=0 | | .3y-.03+.2y=.005 | | 9x^2-8x+6=0 | | -10v-10=-2(8v+-4) | | 3=27/h^2 | | x/10-2=9/20 | | 3p/4=1/5 | | y^2-36y+243=0 | | 7r-2=6r+1 | | 12(.089)+15y=.07 | | s^5+4s^4-32s^2=0 | | 175-75m+47500=50500-150m | | 13c-22=17c+14 | | 6/30=7x/30 | | 5x+13+3x+13=70 | | 590=35x+100 | | -2(y-1)=16 | | 3x-12+5x=2x+6+14 | | 2x^2+4x-837=0 | | 6x^4-3=-7x^2 | | C=4uv | | -8/-36 |